Factors that influence users' purchase intention towards E-commerce platforms among Faculty of Entrepreneurship and Business (FEB)’s students at Universiti Malaysia Kelantan (UMK). - Muhammad Aiman Mohd Zain; Nurul Syazwani Hazman; Nur Ain Nadirah Abd Rahaman; Tan Jia Le (2024)
In recent years, e-commerce has expanded at an exponential rate. With the advancement of technology from time to time, we can see an increasing number of people using e-commerce platforms such as Lazada, Shopee, and Amazon. The objective of this study is to examine factors that influence users’ purchase intention towards e-commerce among the Faculty of Entrepreneurship and Business's (FEB) students at Universiti Malaysia Kelantan (UMK). Three (3) factors are examined: performance expectancy, perceived usefulness, and perceived enjoyment. The research used a convenience sampling technique to collect the data. Besides that, 400 valid responses were collected from UMK FEB’s students through an online Google Form. IBM SPSS was used to analyze the data that had been obtained. The result has clearly shown that performance expectancy, perceived usefulness, and perceived enjoyment had a significant positive effect on purchase intention among UMK FEB’s students.